Clotrimazole Fluidizes Phospholipid Membranes and Localizes at the Hydrophobic Part near the Polar Part of the Membrane - Alessio Ausili; Illya Yakymenko; José A. Teruel; Juan C. Gómez-Fernández (Biomolecules, 2021)
Clotrimazole (1-[(2-chlorophenyl)-diphenylmethyl]-imidazole) is an azole antifungal drug belonging to the imidazole subclass that is widely used in pharmacology and that can be incorporated in membranes. We studied its interaction with 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) phospholipid vesicles by using differential scanning calorimetry and found that the transition temperature decreases progressively as the concentration of clotrimazole increases. However, the temperature of completion of the transition remained constant despite the increase of clotrimazole concentration, suggesting the formation of fluid immiscibility. 1H-NMR and 1H NOESY MAS-NMR were employed to investigate the location of clotrimazole in 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) phospholipid membranes. In the presence of clotrimazole, all the resonances originating from POPC were shifted upfield, but mainly those corresponding to C2 and C3 of the fatty acyl, chains suggesting that clotrimazole aromatic rings preferentially locate near these carbons. In the same way, 2D-NOESY measurements showed that the highest cross-relaxation rates between protons of clotrimazole and POPC were with those bound to the C2 and C3 carbons of the fatty acyl chains. Molecular dynamics simulations indicated that clotrimazole is located near the top of the hydrocarbon-chain phase, with the nitrogen atoms of the imidazole ring of clotrimazole being closest to the polar group of the carbonyl moiety. These results are in close agreement with the NMR and the conclusion is that clotrimazole is located near the water–lipid interface and in the upper part of the hydrophobic bilayer.